The aesthetics of movement in contemporary sculpture art - Abdulsalm Ali, Hana; Karim Muhammad, Azad; Ahmed Khudhur , Karzan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The aim of this study is to examine the aesthetics of movement in contemporary sculpture, focusing on its artistic, historical, and cultural dimensions. Movement in art particularly in kinetic sculpture is deeply connected to philosophical thought and lived experience, serving as a significant expressive medium shaped by the artist’s conceptual vision. The research examines the fundamental question: What is the expressive significance of the aesthetics of movement in contemporary sculpture? The study is broken up into four chapters, which cover the methodological framework for the research, philosophy of beauty and movement, and an analytical examination of the aesthetics of movement in contemporary sculpture. The research explains key theoretical concepts through this framework and ends by identifying critical indicators that demonstrate the significance of movement as a dynamic and influential artistic language in contemporary sculpture practice. DOI: : https://doi.org/10.54633/2333-024-057-021